Treatment of Non-neurogenic Overactive Bladder with OnabotulinumtoxinA: Systematic Review and Meta-analysis of Prospective, Randomized, Placebo-controlled Clinical Trials - Arruda, Raquel Martins; Takano, Claudia Cristina; Girão, Manoel João Batista Castelo; Haddad, Jorge Milhem; Aleixo, Gabriel Francisco; Castro, Rodrigo Aquino (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2018)
We performed a systematic review and meta-analysis of randomized placebo-controlled trials that studied non-neurogenic overactive bladder patients who were treated with 100 units of onabotulinumtoxinA or placebo. The primary purpose of our study was to evaluate the clinical effectiveness with regard to urinary urgency, urinary frequency, nocturia, and incontinence episodes. Our secondary purpose consisted of evaluating the adverse effects. Our initial search yielded 532 entries. Of these, seven studies met all the inclusion criteria (prospective, randomized, placebo-controlled studies, ≥ 3 points on the Jadad scale) and were selected for analysis. For all primary endpoints, the toxin was more effective than placebo (p < 0.0001; 95% confidence interval [95CI]), namely: urgency (mean difference = -2.07; 95CI = [-2.55–1.58]), voiding frequency (mean difference = -1.64; 95CI = [-2.10–1.18]), nocturia (mean difference = -0.25; 95CI = [-0.39–0.11]) and incontinence episodes (mean difference = -2.06; 95CI= [-2.60–1.52]). The need for intermittent catheterization and the occurrence of urinary tract infection (UTI) were more frequent in patients treated with onabotulinumtoxinA than in patients treated with placebo (p < 0.0001). Compared with placebo, onabotulinumtoxinA had significantly and clinically relevant reductions in overactive bladder symptoms and is associated with higher incidence of intermittent catheterization and UTI.
Keywords: overactive bladder; systematic review; botulinum toxin; randomized controlled trials